Osteoporosis is the cause of spontaneous humeral fracture in dairy cows from New Zealand. Issue 1 (January 2023) - Wehrle-Martinez, Alvaro; Lawrence, Kevin; Back, Penny J.; Rogers, Chris W.; Gibson, Michaela; Dittmer, Keren E.
Outbreaks of humeral fractures in dairy cows have been reported in New Zealand for several years. Gross, histologic, and histomorphometric findings in the humerus from primiparous cows with spontaneous humeral fracture were compared to age-matched control cows. Affected cows had a complete nonarticular spiral fracture of the humerus. Histologically affected humeri had a thicker growth plate with abnormal architecture, thinner cortex with increased abnormal resorption, increased resorption in the distal humerus, decreased trabecular density, abnormal trabecular architecture, presence of growth arrest lines and woven bone formation. Histomorphometry showed reduction in bone volume, trabecular perimeter, and trabecular width. Cows grazed on fodder beet had thicker growth plates with an abnormal appearance compared with cows grazed on pasture, and cows with low/marginal liver copper concentration had more resorption cavities in the distal humerus and thinner cortical bone compared with cows with adequate liver copper concentration. Decreased trabecular density (OR = 249.5), abnormal cortical resorption (OR = 54.2), presence of woven bone formation in the proximal metaphysis (OR = 37.2), and the number of resorption cavities in the distal humerus were significantly associated with a high probability of fracture. Ribs had enlargement of the costochondral junction with fractures in different stages of healing. Histology of the ribs revealed abnormal growth plate appearance, presence of fracture lines, callus tissue, fibrosis, and microfractures. Cows with humeral fracture have osteoporosis due to decreased bone formation and increased bone resorption, likely associated with inadequate feed quality and perhaps copper deficiency leading to a reduction in bone strength and fracture.